The quasi-continuous exhaust regime in JET - M. Faitsch; M. Dunne; E. Lerche; P. Lomas; I. Balboa; P. Bilkova; P. Bohm; A. Kappatou; D. Kos; B. Labit; S. Menmuir; O. Sauter; et al. (Nuclear Fusion)
The quasi-continuous exhaust (QCE) regime is a regime that is naturally type-I ELM-free. It combines the high density at the plasma edge needed for power exhaust with the high normalised energy confinement typical for H-mode operation. In the QCE regime large-scale ELMs are avoided and high-frequency, low-amplitude filaments are present leading to the name-giving quasi-continuous edge transport of particles and energy. This contribution reports that for the first time the QCE regime was successfully achieved in JET with a metal wall. Moreover, it was demonstrated in the recent JET deuterium-tritium campaign DTE3 that the regime is compatible with D–T operation. Porting the QCE regime to JET strongly benefited from the experimental and modelling efforts at the medium sized tokamaks ASDEX Upgrade and TCV. Using the physics picture developed from the ASDEX Upgrade experimental results, the route to the QCE regime in JET reported here is following closely the approach that was successful in ASDEX Upgrade. First, strong plasma shaping—large elongation and triangularity and the highly correlated closeness to double null—is developed. Second, sufficient fuelling to achieve high enough density at the pedestal foot, close to the separatrix, is applied. In addition, neon seeding proved to be very beneficial to avoid type-I ELMs when reducing the main ion fuelling.